(untitled) (Academicia Globe: Inderscience Research, 2022)
This article provides clear and detailed information about corneal lesions in endoctrine ophthalmopathy. In this article facts about the causes of this illness are mentioned, in turn, ways to prevent and cure this illness are also clarified.